Effective Strategy to Reduce Import Level of Fashion Products by Coaching Millennial Students Independently Creative Islamic Boarding School in Indonesia - Muhammad Fahmul Iltiham; Wiwin Ainis Rohtih (MALIA: Jurnal Ekonomi Islam, 2023)
This research aims to recognize the role of Islamic boarding schools (pesantren) in nurturing entrepreneurship as an effort to overcome competition from foreign products. Islamic boarding schools have the potential as educational institutions that shape individuals who are religious and independent, aligning with the goals of the entrepreneurship program. Enhancing entrepreneurship in Islamic boarding schools is a necessity to ensure that students (santri) are not only competent in religious aspects but also possess economic self-reliance. This is expected to have a significant impact on the economy, especially in creating entrepreneurs from among the students. With a large number of Islamic boarding schools and students, these institutions have a strategic potential to support national economic development. Many Islamic boarding schools have established cooperatives, developed small and medium-sized business units or industries, and have business incubators. The research method used is qualitative, employing data collection techniques through observation, interviews, and documentation. The study was conducted at an Islamic boarding school in Pasuruan Regency. The results indicate that Islamic boarding schools in Pasuruan Regency play a crucial role in training modern industrial entrepreneurs by establishing various business units such as food, clothing manufacturing, and accessories. Entrepreneurship programs empower students and the community, improve their well-being, and create job opportunities. The involvement of students in entrepreneurship at the Islamic boarding school has resulted in alumni establishing similar businesses that serve the broader Pasuruan Regency area.